2020
DOI: 10.3390/jcm9072220
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Whole-Exome Sequencing as a Diagnostic Tool in a Neonatal/Pediatric Intensive Care Unit

Abstract: Genetic disorders are the leading cause of infant morbidity and mortality. Due to the large number of genetic diseases, molecular and phenotype heterogeneity and often severe course, these diseases remain undiagnosed. In infants with a suspected acute monogenic disease, rapid whole-exome sequencing (R-WES) can be successfully performed. R-WES (singletons) was performed in 18 unrelated infants with a severe and/or progressing disease with the suspicion of genetic origin hospitalized in an Intensive Care Unit (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 44 publications
2
55
0
Order By: Relevance
“…The high diagnostic rate and 180-day mortality rate derived from this work proved that NGS was an effective tool for critically ill infants suspected of a genetic disorder ( French et al, 2019 ; Australian Genomics Health Alliance Acute Care Flagship et al, 2020 ; Śmigiel et al, 2020 ). Firstly, our diagnostic yield was similar to those reported in Western countries; with diagnostic rates of 36–57% ( Willig et al, 2015 ; Meng et al, 2017 ; Powis et al, 2018 ; Brunelli et al, 2019 ; French et al, 2019 ) even though there were differences among the disease spectrum.…”
Section: Discussionmentioning
confidence: 81%
“…The high diagnostic rate and 180-day mortality rate derived from this work proved that NGS was an effective tool for critically ill infants suspected of a genetic disorder ( French et al, 2019 ; Australian Genomics Health Alliance Acute Care Flagship et al, 2020 ; Śmigiel et al, 2020 ). Firstly, our diagnostic yield was similar to those reported in Western countries; with diagnostic rates of 36–57% ( Willig et al, 2015 ; Meng et al, 2017 ; Powis et al, 2018 ; Brunelli et al, 2019 ; French et al, 2019 ) even though there were differences among the disease spectrum.…”
Section: Discussionmentioning
confidence: 81%
“…One challenge for clinicians is the time required for various NGS tests, including WES, whole‐genome sequencing, and targeted‐gene panels, to provide results. Rapid WES can often provide results within 2 weeks and therefore may impact clinical decision‐making for a patient hospitalized with ALF 23 . Chung et al 24 reported that the median turnaround for rapid WES was 11 days and changed clinical management in 88% of patients with suspected monogenic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Proband’s DNA isolated from amniocytes was subjected to NGS-based WES performed in the RAPID form according to a previously described protocol [ 7 ]. Venous blood samples were collected from the proband’s parents.…”
Section: Methods Of Genetic Analysesmentioning
confidence: 99%